APPLICATION OF PROGESTERONE PROFILES IN THE ASSESSMENT OF POST ARTIFICIAL INSEMINATION FERTILITY IN CATTLE - Singh, Narinder; Singh, Khushpreet; Mavi, Gurjot Kaur; Kumar, Ajeet (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to investigate success of AI in relation to progesterone concentrations with respect to the timing of inseminations or heat detection in the field. Milk samples were collected for progesterone assay from 149 crossbred cows subjected to AI. The milk progesterone concentrations were estimated by RIA to access the reproductive status of the cows. On the day of AI, progesterone concentrations were less than 1.0 nmol/L (Low) in 51% samples and more than 3.00 nmol/L (High) in 18%. Rest 31 % samples showed intermediate progesterone (1.01 to 2.99 nmol/L) suggesting that these cows were nor in proper heat at the time of AI. On the basis of two samples (day 0 and day 10-12 post AI), 50% cows had low progesterone concentrations on the day of AI and high in the second sample, indicating that these cows were inseminated during estrus and ovulated subsequently. Whereas, 12% cows had high progesterone in both the samples suggesting that at the time of AI these cows were either in the luteal phase or had luteal cyst. Remaining 37% cow had intermediate progesterone concentrations on both the occasions suggesting that they were having either developing or regressing or malfunctioning corpora lutea or partial luteal cyst. Perusal of observations on progesterone concentrations showed that 18% of inseminations were done during luteal phase and another 30% were done at some inappropriate time of heat, thus suggesting that high proportion (48%) of cows under field conditions were inseminated while not in proper heat.